Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18203/2349-3933.ijam20171477
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria as an early marker of left ventricular hypertrophy in type 2 diabetes mellitus

Abstract: Background: Microalbuminuria and left ventricular hypertrophy (LVH) have both been shown independently to be associated with increased cardiovascular (CVS) mortality in type 2 diabetes mellitus (DM) patients. This cross-sectional study was conducted to examine whether microalbuminuria is associated with LVH in non-hypertensive type 2 DM patients with early or no diabetic nephropathy.Methods: 100 patients of type 2 DM were studied. Patients with Hypertension (BP >140/90 mm hg or on anti-hypertensive medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
4
1
0
Order By: Relevance
“…In the present study, the mean fasting blood sugar (FBS), post-prandial blood sugar (PPBS), and HbA1c level was significantly lower in normoalbuminuric group compared to microalbuminuric group. This finding is concordant to the study by Kanwar BS et al [11].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the mean fasting blood sugar (FBS), post-prandial blood sugar (PPBS), and HbA1c level was significantly lower in normoalbuminuric group compared to microalbuminuric group. This finding is concordant to the study by Kanwar BS et al [11].…”
Section: Discussionsupporting
confidence: 93%
“…Echocardiography parameters like left ventricular internal dimension in systole (LVIDs), left ventricular endsystolic volume (LVESV), ejection fraction, deceleration time (DT), and acceleration time (AT) were comparable between the groups in our study. This is in concordance to the studies of Kanwar BS et al, Shogade TT et al, and Swoboda PP et al [11,12,19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Kanwar et al in their crossectional study done on 100 normotensive Indians with diabetes mellitus reported that the correlation between increased albuminuria and LVMI was found to be statistically significant (P value < 0.001) and the LV mass significantly increased as albuminuria increased along the continuum of normoalbuminuria to macroalbuminuria [30]. In our study, which is the first of its kind in Africa, we found that persistent microalbuminuria has a strong association with LV geometry remodeling, that microalbuminuric normotensive diabetics are three times more likely to have LV geometry remodeling than normoalbuminuric group.…”
Section: Discussionmentioning
confidence: 95%